2022
DOI: 10.1093/bib/bbac049
|View full text |Cite
|
Sign up to set email alerts
|

CoverageMaster: comprehensive CNV detection and visualization from NGS short reads for genetic medicine applications

Abstract: CoverageMaster (CoM) is a copy number variation (CNV) calling algorithm based on depth-of-coverage maps designed to detect CNVs of any size in exome [whole exome sequencing (WES)] and genome [whole genome sequencing (WGS)] data. The core of the algorithm is the compression of sequencing coverage data in a multiscale Wavelet space and the analysis through an iterative Hidden Markov Model. CoM processes WES and WGS data at nucleotide scale resolution and accurately detects and visualizes full size range CNVs, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is achievable with tools such as CoNIFER ( Krumm et al, 2012 ), exomeCopy ( Love et al, 2011 ), CNVkit ( Talevich et al, 2016 ), cn. MOPS ( Klambauer et al, 2012 ), CNest ( Fitzgerald and Birney, 2022 ), CNVind ( Kusmirek and Nowak, 2022 ), CoverageMaster ( Rapti et al, 2022 ) and EXCAVATOR2 ( D’Aurizio et al, 2016 ; D’Aurizio et al, 2018 ). More recently, Olfe et al have demonstrated CTLA-4 insufficiency due to a novel CTLA-4 deletion using ClinCNV ( German and Stephan, 2019 ; Olfe et al, 2023 ), further highlighting the synergy of CNV calling with WES analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is achievable with tools such as CoNIFER ( Krumm et al, 2012 ), exomeCopy ( Love et al, 2011 ), CNVkit ( Talevich et al, 2016 ), cn. MOPS ( Klambauer et al, 2012 ), CNest ( Fitzgerald and Birney, 2022 ), CNVind ( Kusmirek and Nowak, 2022 ), CoverageMaster ( Rapti et al, 2022 ) and EXCAVATOR2 ( D’Aurizio et al, 2016 ; D’Aurizio et al, 2018 ). More recently, Olfe et al have demonstrated CTLA-4 insufficiency due to a novel CTLA-4 deletion using ClinCNV ( German and Stephan, 2019 ; Olfe et al, 2023 ), further highlighting the synergy of CNV calling with WES analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lot of algorithms have been developed to detect CNVs from sequencing data, high resolution version of aCGH is still an appropriate methodology for the analysis of chromosome aberrations in a cohort (Corallo et al, 2021; Retterer et al, 2015). The application of whole‐exome sequencing (WES) surely reduced related costs of sequencing while there is also deficiency considering the restricted detection in exomic space and the data processing itself (Rapti et al, 2022). Chromosome aberrations in MRKH patients has been only analyzed using WES data in the Chinese population (Chen, Zhao, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that mNGS exhibits limited ability for structural rearrangement and CNV detection. However, numerous techniques and algorithms have been put forward, such as Sat-BSA (SVs associated with traits), CoverageMaster, and KNNCNV (K-Nearest Neighbor-based CNV detection) (37)(38)(39). Besides, the sensitivity and specificity of mNGS require further improvement, and combining mNGS with other assays is a promising strategy.…”
Section: Discussionmentioning
confidence: 99%